Perceptions of Campus Safety Policies: Contrasting the Views of Students with Faculty and Staff - Kyle, Michael J. (American journal of criminal justice, 2017)
A series of recommendations to colleges and universities concerning safety, security, and incident response policies emerged in the aftermath of several high-profile tragic events on campuses. Although these appear as “common sense” solutions to the perceived risks, little is known about the level of support the normative recommendations receive from the very people they are intended to protect. This study utilizes survey data from a Midwestern university to examine the level of support expressed by students, faculty, and staff for commonly recommended campus safety policies and procedures. Multivariate models are used to compare the viability of explaining levels of support through the lenses of respondent demographics and experiences, fear of crime, and perceptions of campus public safety. Although attitudes significantly differed, students were substantively quite similar to faculty and staff. However, the factors that were hypothesized to influence support for campus safety initiatives (i.e., prior victimization, fear of crime, protective measures, perception of disorder, race, sex, and age) were not consistently predictive. This suggests that campus policymakers and state legislatures may be well served to consider the opinions of campus community members before imposing what may be unpopular policies that have questionable efficacy.